Penanggulangan Sampah Plastik Di Desa Tangkas Kabupaten Klungkung Perspektif Pendidikan Hindu - Putri, Ida Ayu Nindia Brahmani; Arini, Ni Wayan; Dewi, Ni Wayan Sri Prabawati Kusuma (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The problem of plastic waste, lately continues to be a concern by the government of Tangkas Village, Klungkung Regency. This is because disposable plastic waste that is discarded carelessly by the surrounding community has caused disruption to the palemahan system (environment) in Tangkas Village. Because of concern over the problem, the Desa Adat and the local Desa Dinas, established the Darma Winangun Community Self-help Group which concentrated on the conservation of education-based campuses, particularly in the prevention of disposable plastic waste. After five years of running its various programs, the Dharma Winangun Community Self-Help Group still exists today, although it faces several obstacles. Globally, the various programs above can overcome and change people's behavior to not be consumptive towards the use of plastic waste, especially those that are disposable and switch to the use of environmentally friendly products. However, in its implementation, these various programs encountered several obstacles namely, (1) internal obstacles; there are still some communities whose awareness has not yet been awakened to the danger of disposable plastic waste, limited human resources to process waste gradually, (2) external constraints; limited capacity of space and machinery in landfills (TPS), as well as in the ecotour program also face a shortage of implementation team staff.